MENINGKATKAN PELUANG KERJA LULUSAN SMK MELALUI PELATIHAN UAV UNTUK MENYELARASKAN DENGAN KEBUTUHAN INDUSTRI - Martina, Ayu; Widanto, Muhammad Hadi; Rosadi, Imron (An-Nizam, 2025)
The high unemployment rate among vocational high school graduates, particularly in the aviation sector, indicates a significant gap between students’ competencies and industry needs. This condition highlights the urgency of technology-based training to enhance graduates’ competitiveness, especially in the Industry 4.0 era marked by the rapid development of Unmanned Aerial Vehicle (UAV) technology. This community service program was carried out at SMK Gutama Jakarta, selected as a strategic partner due to its lack of prior UAV learning experience yet strong commitment to improving student competencies. The main objective of this program was to provide practical skills in UAV construction, understanding the principles of UAV electrical systems, introducing UAV simulators as interactive learning media, and developing knowledge of UAV supporting systems. The program was implemented through several stages, including socialization, UAV construction practices, electrical system training, simulator usage, and flight testing. The results showed a significant increase in students’ knowledge, with pre-test and post-test scores improving by 35.7%, along with enhanced technical skills in assembling and operating UAVs. Furthermore, evaluation questionnaires indicated a high level of student satisfaction, particularly in the hands-on training component. In conclusion, UAV training successfully improved the attitudes, knowledge, and skills of SMK Gutama students, preparing them to better enter the industrial workforce. Therefore, similar programs should be carried out continuously with school support to establish an independent vocational learning model aligned with industry needs.